Livre improvisação como processo de composição musical: elaboração de performances musicais - Meira, Antônio Carlos Santos (2017)
This research is a proposal directed at the practice of free improvisation, elaboration of performances and compositions in the contemporary music perspective. Seeking throughout the text to understand this musical practice in context of its emergence, aesthetic influences and its development to the present. This text is divided into three parts. The first part discusses through a literature review the nascent aesthetics of free improvisation. The second part analyzes the poetics of content related to sound and the initiation of poetry within the form. The third part is the development of process involving new technologies and analysis of free improvisation sessions.